Resonance Suppression of Multi-Inverter Systems Based on Global Admittance Reshaping - Jike Zhang; Guifa Wang; Ruiming Liu; Tianchen Zhang; Jiankang Wang (Active and Passive Electronic Components)
This paper proposes an active damping control method based on converter-side current feedback to mitigate the resonance issue in multi-inverter grid-connected systems caused by coupling with the grid impedance. The method aims to address the reduction in grid power quality by utilizing an active damping device without modifying the hardware and software of the grid-connected inverters. By introducing an additional small-capacity power electronic device in parallel, the proposed method establishes two parallel admittances at the common connection point, creating specific conduction paths for system harmonics and reshaping the overall system admittance. In parallel operation of two photovoltaic grid-connected inverters with different capacities, the access of the inherent admittance and virtual admittance of the source damper reduces the harmonic distortion rate of the grid-connected current from 19.81% to 2.04% and from 15.86% to 0.52%, respectively. Simulation results validate the effectiveness and correctness of the proposed strategy.